Trend analysis and factors associated with biological injuries among health care workers in Southern Italy - Cofini, Vincenza; Capodacqua, Alberto; Calisse, Santina; Galassi, Italia; Cipollone, Lora; Necozione, Stefano (La Medicina del Lavoro, 2018)
Background: Biological injuries are the most common and serious among health care workers. Objectives: This study aims to estimate the injuries’ incidence, job distribution and temporal trend in a hospital in Southern Italy. Methods: Data on accidents, collected from January 2010 to December 2016, were analyzed. Poisson distribution was used to calculate incidence rates and respective 95% confidence intervals. Trends were analyzed using the Joinpoint regression model. A multiple logistic regression model was used to identify factors associated with injuries. Results: Three hundred and thirty-five injuries were reported from 2010 to 2016, occurring mainly in the morning (54%) and frequently caused by needlestick (70%). We observed a significant decline in the incidence rates of the total amount of injuries (ACP=-11.3; 95% CI: -16.3 - -5.9), for nurses (ACP=-15.7; 95% CI: -24.3 - -6.2) and for health and social care assistants (ACP=-13.2; 95% CI: -23.1 - -2.0). Among male physicians the risk of biological accident was higher than female physicians (OR=3.67; 95% CI:1.9-7.1), while among male nurses the risk was lower than among female nurses (OR=0.31; 95% CI: 0.17-0.59). For the nursing category, “afternoon” and “night” represented risk factors with OR=2.19 (95% CI: 1.2-3.7) and OR=8.8 (95% CI: 3.4-22.8) respectively. For physicians, surgical intervention was a risk factor (OR=7.71; 95% CI: 3.2-18.4). Conclusions: Our findings confirm the need for continuous monitoring and improved control of work-related exposures, both for health and the associated costs.